Developmental changes in gut microbiota and enzyme activity predict obesity risk in rats arising from reduced nests - Šefčíková, Z; Bujňáková, D; Raček, Ľ; Kmet, V; Mozeš, Š (Physiological research, 2011)
The aim of the study was to assess the impact of preweaning overnutrition upon the ontogeny of intestinal microbiota, alkaline phosphatase activity (AP) and parameters of growth and obesity in male Sprague-Dawley rats. We tested whether intestinal characteristics acquired in suckling pups could programme the development of enhanced fat deposition during normalized nutrition beyond weaning. Postnatal nutrition was manipulated by adjusting the number of pups in the nest to 4 (small litters--SL) and 10 (normal litters--NL). In the postweaning period both groups were fed with a standard diet. The jejunal and colonic Lactobacillus/Enterococcus (LAB) and the Bacteroides/Prevotella (BAC) were determined using the FISH technique, and the jejunal AP activity was assayed histochemically. At 15 and 20 days of age the SL pups became heavier, displayed increased adiposity accompanied by significantly higher LAB and lower numbers of BAC and with higher AP activity in comparison with rats nursed in NL nests. These differences persisted to day 40 and withdrawal of the previous causal dietary influence did not prevent the post-weaning fat accretion. These results reveal the significance of early nutritional imprint upon the gut microbial/functional development and allow better understanding of their involvement in the control of obesity.
Keywords: Litter Size; střeva; Male; adipozita; metagenom; Obesity; potkani Sprague-Dawley; Alkaline Phosphatase; Lactobacillus; alkalická fosfatasa; obezita; Bacteroides; mužské pohlaví; Body Weight; krysa rodu Rattus; Metagenome; Animals; velikost vrhu; Enterococcus; zvířata; Adiposity; Rats; Risk; Prevotella; Weaning; Intestines; riziko; tělesná hmotnost; odstavení; Rats, Sprague-Dawley